PERLINDUNGAN HUKUM PEKERJA ATAS KETIDAKSESUAIAN UPAH LEMBUR (STUDI KASUS K-THENGONO DESIGN STUDIO) - Sisworo, Nathasya; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
The Constitution expressly provides protection for workers to obtain fair compensation and treatment in an employment relationship. This provision is also further regulated in Article 88 of the Manpower Law. But in fact, there are many violations in the payment of wages for workers, including in terms of overtime pay. This happened to workers at K-Thengono Design Studio due to the discrepancy between the calculation of overtime wages made by the company and the provisions stipulated in the applicable Law (UU) and implementing regulations. On this basis, the author conducts this research with the aim of reviewing legal protection for workers who experience discrepancies in overtime wages. This research is focused on the formulation of problems related to how legal protection can be taken by workers if they receive overtime wages that are not in accordance with applicable laws and regulations, with the methodology used is normative juridical with descriptive analysis and doctrinal research. The result of this research is that K-Thengono Design Studio has violated the provisions of labor law regarding the provision of inappropriate overtime pay. In addition, there has also been a violation of the agreement due to not hiring according to the duties and functions in the agreement. With this basis, workers can take legal action by reporting to the labor office. If then the settlement cannot be done through mediation, the worker can take legal action by reporting to the labor office.Keywords: Legal Protection, Wages, Workers